1993
DOI: 10.1021/bi00090a028
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of binding of multiple HIV-1 Rev monomeric proteins to the Rev responsive element

Abstract: Recombinant HIV-1 Rev protein was overexpressed in Escherichia coli using translational coupling to the beta-glucuronidase gene and demonstrated to interact with high affinity and specificity with the Rev responsive element (RRE). A complex Rev-dependent binding pattern was observed using the gel shift assay which could be simplified to one or two primary bands in the presence of stoichiometric concentrations of RRE. Competition of these bands with a series of homopolymer RNA species demonstrated that Rev is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 48 publications
(66 reference statements)
4
68
1
Order By: Relevance
“…RNA gel retardation assays were performed using in vitro transcribed 32 P-labeled CD83-derived probes, MS2 competitor RNA, and GST fusion protein as described previously (46), except that RNA-protein complexes were resolved on 4 or 6% native polyacrylamide gels. Supershift assays were performed using anti-HuR (clone 19F12, Invitrogen) and anti-FLAG (Sigma) monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…RNA gel retardation assays were performed using in vitro transcribed 32 P-labeled CD83-derived probes, MS2 competitor RNA, and GST fusion protein as described previously (46), except that RNA-protein complexes were resolved on 4 or 6% native polyacrylamide gels. Supershift assays were performed using anti-HuR (clone 19F12, Invitrogen) and anti-FLAG (Sigma) monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Although the RxRE harbors a single high affinity binding site for Rex, it has been suggested that multiple Rex proteins bind to a single mRNA molecule prior to export via cooperative protein-protein and protein-RNA interactions (76,77). There are two regions in both Rex-1 and Rex-2 that serve as multimerization domains (54,64,78).…”
Section: Rex Proteins: Structure Subcellular Localization and Functmentioning
confidence: 99%
“…Then the export of RNA is carried out by Crm1 nuclear export pathway [17]. First Rev oligomerizes onto the RRE to form a ribonucleoprotein (RNP) complex of 200-300 kDa containing 8-10 Rev molecules [18][19], that binds Crm-1 (exportin-1), GTP-bound Ran, and other host cell proteins via the Rev nuclear export sequence (NES), to promote nuclear export [20]. Structure of REV contain 116 a.a in a single chain [21].…”
Section: Introductionmentioning
confidence: 99%